Mga kuwentong-bayan ng katimugang Pilipinas - Casanova, Arthur P. (Arthur de la Pena); Esteban, Rolando C. 1959-; Esteban, Ivie C. (Mandaluyong City Anvil Publishing, Inc., 2011)
Collection of folktales from Mindanao.
Also published in English: Folktales of Southern Philippines / Rolando C. Esteban, Arthur P. Casanova, Ivie C. Esteban.
Keywords: Tales -- Philippines -- Mindanao Island; Folklore -- Philippines